Effect of non-cephalosporin antibiotic prophylaxis on the risk of periprosthetic joint infection after total joint replacement surgery: a retrospective study with a 1-year follow-up - Meeri Honkanen; Simo Sirkeoja; Matti Karppelin; Antti Eskelinen; Jaana Syrjänen (Elsevier, 2023)
Summary: Background: Cephalosporins are recommended as first-line antibiotic prophylaxis in total joint replacement surgery. Studies have shown an increased risk for periprosthetic joint infection (PJI) when non-cephalosporin antibiotics have been used. This study examines the effect of non-cephalosporin antibiotic prophylaxis on the risk for PJI. Methods: Patients with a primary hip or knee replacement performed from 2012 to 2020 were identified (27 220 joint replacements). The primary outcome was the occurrence of a PJI in a one-year follow-up. The association between perioperative antibiotic prophylaxis and the outcome was examined using logistic regression analysis. Discussion: Cefuroxime was used as prophylaxis in 26,467 operations (97.2%), clindamycin in 654 (2.4%) and vancomycin in 72 (0.3%). The incidence of PJI was 0.86% (228/26,467) with cefuroxime and 0.80% (6/753) with other prophylactic antibiotics. There was no difference in the risk for PJI with different prophylactic antibiotics in the univariate (OR 1.06, 95% CI 0.47-2.39) or multivariable analysis (OR 1.02, 95% CI 0.45-2.30). Conclusion: Non-cephalosporin antibiotic prophylaxis in primary total joint replacement surgery was not associated with an increased risk for PJI.